Internet of Things: An Implementation and Its Challenges in Malaysia - Wan Isni Sofiah, Wan Din; Zalili, Musa (INSIGHT - Indonesian Society for Knowledge and Human Development, 2018)
To date, the Internet becomes one of the technologies that is rapidly evolving and changing. It has become trending over the world. The Internet of Thing is a mechanism composed of devices, sensors, networks, cloud storage, and application. Each device able to communicate with another device over the Internet to share the information and accomplished some objectives. IoT is known as one of the new future technologies and were gaining attention from various fields over the countries. Malaysia is one of the countries in the planning stage to increase the development of IoT, which is equivalent to other countries with the emerging IoT applications development. However, it was not easy to develop IoT devices due to some issues and challenges in implementing IOT devices. This paper addresses the major concern and challenges in IOT and the solution how to overcome these issues. The future trends and applications of IoT were also briefly discussed in this paper for gaining more in-depth knowledge about the IOT technology.